Pengaruh Kepercayaan dan Gaya Hidup Terhadap keputusan Pembelian Menggunakan Pinjaman Online Shopee Paylater - Silvy Waroka; Arif Fadila (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out, analyse, and explain the description of each variable, the magnitude of the relationship between Trust and Life Style on the Customer Shopee Paylater, and the amount of influence partially and simultaneously Trust and Life Style on Online Loans Shopee Paylater. By using quantitative methods and using descriptive analysis and verification. The analysis tool used is path analysis (path analysis). Samples taken were 170 respondents. Data collection techniques used are literature and field data collection by distributing questionnaires online. The results showed that Trust and Life Style have a strong relationship. As well as Trut and Life Style have a positive and significant effect on Purchasing Decision on Online Loans Shopee Paylater.